Miraculous recovery of perioperative acute uniocular loss of vision following spine surgery in prone position - Malik, Sakil; Chatterjee, Jishnu; Mukherjee, Debanjana; Chowdhury, Dipanjan (International Surgery Journal, 2025)
An 18 years old female came to emergency with low back pain radiating to left lower limb for 8 months. The patient had no comorbidities as such and was hemodynamically stable with HR-72/min, BP-120/60 mmHg, Spo2-98% in room air, RBS-125 mg/dl. Patient was diagnosed with L5-S1 PIVD with Lumbar Canal Stenosis and was planned for L5-S1 instrumented spinal Stabilization with L5 laminectomy and discectomy under general anaesthesia. Preoperative status of the patient was stable. Perioperatively patient had uniocular left sided complete loss of vision for 3 days following which gradual improvement of vision to normal restoration of vision achieved after 4 months along with a diagnosis of left optic neuritis with severe retino-optic nerve pathway dysfunction.